2022
DOI: 10.1177/00315125221145220
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Kinetic and Kinematic Finger Individuation Capability in Children With Hemiplegic Cerebral Palsy

Abstract: While fine manual dexterity develops over time, the extent to which children show independent control of their digits in each hand and the impact of perinatal brain injury on this individuation have not been well quantified. Our goal in this study was to assess and compare finger force and movement individuation in 8–14 year old children with hemiplegic cerebral palsy (hCP; n = 4) and their typically developing peers (TD; n = 10). We evaluated finger force individuation with five independent load cells and cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Previous studies of grasping have shown that children with CP do not develop typical force coordination patterns ( Eliasson et al, 1991 ), and the kinematics of their reaching movements are more segmented and do not show anticipatory shaping of the fingers ( Rönnqvist and Rösblad, 2007 ). Children with CP also show less individuation between the fingers in the paretic hand ( McCall et al, 2022 ). A recent study compared an adult CP group to healthy controls ( Kong et al, 2019 ), and found that the CP group showed smaller maximal forces and higher indices of finger interdependence (enslaving) (i.e., less individuated finger force production in the CP group), while the indices of multi-finger synergies stabilizing total finger forces were not significantly different from those of a control group.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of grasping have shown that children with CP do not develop typical force coordination patterns ( Eliasson et al, 1991 ), and the kinematics of their reaching movements are more segmented and do not show anticipatory shaping of the fingers ( Rönnqvist and Rösblad, 2007 ). Children with CP also show less individuation between the fingers in the paretic hand ( McCall et al, 2022 ). A recent study compared an adult CP group to healthy controls ( Kong et al, 2019 ), and found that the CP group showed smaller maximal forces and higher indices of finger interdependence (enslaving) (i.e., less individuated finger force production in the CP group), while the indices of multi-finger synergies stabilizing total finger forces were not significantly different from those of a control group.…”
Section: Introductionmentioning
confidence: 99%
“…Hand function is one of the most complex components of the human motor system [1][2][3][4][5]. Grasping objects, for example, often begins with visual perception and generation of a motive to reach [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, this technique is a gross assessment that does not detect subtle deficits in hand function [25][26][27]. Moreover, there is no commercially available digital dynamometer designed to measure dexterous modulation of individual finger strength, which is a core component of tasks required for daily living [1,2,[28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations